A prospective study of factors associated with successful maturation of arteriovenous fistulas for hemodialysis - Fuentes Nadia Elizabeth Saavedra; Blanco Juan Reyna; Garcia Gloria Queipo; Navarro Monserrat Perez; Gonzalez Claudia Lerma; Valdez-Ortiz Rafael (Journal of Ultrasonography)
Our objective was to determine the factors associated with the successful maturation of arteriovenous fistulas during hemodialysis.